PEMBERDAYAAN SISWA SEBAGAI PEER EDUCATOR KESEHATAN REPRODUKSI REMAJA - Sri Susanti; Cholik Harun Rosjidi; Metti Verawati (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2019)
The Community Service Program aims to form a trained peer counselor by providing knowledge and skills to peer counselors on adolescent reproductive health and ways to deal with the problem. Design to achieve these goals by training some students to become peer counselors about reproductive health. The main material for this training is Adolescent Reproductive Health and the ways to overcome the problem, as well as how to become a peer counselor. The program target is a member of the OSIS SMK PGRI 1 Ponorogo. The training is conducted 1 day and mentoring is carried out 1 day. The number of students trained by 20 students as peer counselors. The training results showed 95% of students increased significantly the reproductive health knowledge score. And 100% of students are able to act as a peer educator effectively. The peer educator program should be an extra-curricular activity in all schools both junior and senior high school to prevent unhealthy sexual behavior in adolescents.